Early Infant Diagnosis Sample Management in Mashonaland West Province, Zimbabwe, 2017. (26th July 2018) - Mugauri, Hamufare; Mugurungi, Owen; Chadambuka, Addmore; Juru, Tsitsi; Gombe, Notion Tafara; Shambira, Gerald; Tshimanga, Mufuta
Abstract : Background. In 2016, Mashonaland West Province had 7.4% (520) dried blood spot (DBS) samples for early infant diagnosis (EID) rejected by the Zimbabwe National Microbiology Reference Laboratory (NMRL). The samples were suboptimal, delaying treatment initiation for HIV-infected children. EID is the entry point to HIV treatment services in exposed infants. We determined reasons for DBS sample rejections and suggested solutions. Methods. A cause-effect analysis, modelled on Ishikawa, was used to identify factors impacting DBS sample quality. Interviewer-administered questionnaires and evaluation of sample collection process, using Standard Operating Procedure (SOP) was conducted. Rejected samples were reviewed. Epi Info™ was used to analyze findings. Results. Eleven (73.3%) facilities did not adhere to SOP and (86.7%) did not evaluate DBS sample quality before sending for testing. Delayed feedback (up to 4 weeks) from NMRL extended EID delay for 14 (93.3%) of the facilities. Of the 53 participants, 62% knew valid sample identification. Insufficient samples resulted in most rejections (77.9%). Lack of training (94.3%) and ineffective supervision (69.8%) were also cited. Conclusion. Sample rejections could have been averted through SOP adherence. Ineffective supervision, exacerbated by delayed communication of rejections, extended EID delay, disadvantaging potential ART beneficiaries. Following this study, enhanced quality control through perstage evaluations was recommended to enhance DBS sample quality.